ANALISIS KINERJA PEMBIMBING MANASIK BERBASIS PENGUASAAN MATERI : (Studi Pada KBIHU Aisyiyah Kabupaten Sleman) - Rojiki Rojiki (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2022)
This research was conducted on pilgrims from KBIHU Aisyiyah, Sleman Regency which depart in the year 144- H / 2020-M as many as 120 people that it’s used 93 respondents by the Slovin Method. This study used primary data through a questionnaire instrument. Test the validity and reliability used SPSS 25 software tools. Meanwhile, to test Confirmatory Factor Analysis (CFA) and data analysis using SmartPLS 3.2.8. The results of this study indicate that: Learning Method does not affect the Effectiveness of Material Mastery, Experience has a positive and significant effect on the Effectiveness of Material Mastery, Motivation has a positive and significant effect on the Effectiveness of Material Mastery, Learning Method has a positive and significant effect on the Performance of Counselors, Experience has no effect on the Performance of Counselors, Motivation does not affect the Performance of Counselors. Furthermore, the results of the mediation analysis show that the effectiveness of the guidance is able to provide a mediating effect between the coach's experience and the motivation to the performance of the coach. But the mediating effect does not occur on the effect of the learning method on the coach's performance.